Alternative processing methods of hybrid porous scaffolds based on gelatin and chitosan. (February 2020) - Perez-Puyana, Víctor; Rubio-Valle, José Fernando; Jiménez-Rosado, Mercedes; Guerrero, Antonio; Romero, Alberto
Abstract: The present work focuses on the development of scaffolds based on gelatin and chitosan using different protocols based on the general processing of phase separation, derived from the fabrication of hydrogels and freeze-drying. The scaffolds were produced with 1 wt% of two different biopolymers, i.e. gelatin (GE) and chitosan (CH), and the influence of the ratio between the two polymers was analyzed, as well as three different processing methods. This analysis consisted in assessing their mechanical properties by strain and frequency sweep tests, and comparing their microstructure and fiber arrangement by means of porosimetry, scanning electron microscopy (SEM) and degree of crosslinking. The results obtained show that the properties of the scaffolds were strongly dependent on the proportion of the raw materials used, as well as on the processing method. As a result, it was found that synergy occurred when a 1:1 gelatin:chitosan ratio was used, and when the temperature was increased, since it favors the solubilization of biopolymers and their interaction during mixing.